Research on the Protective Performance of Tinning Layer on Electrical Copper Bars - FENG Ye-lin, DING Yun-hu, MAO Zu-guo, HUANG Xing-lin, WANG Zhu-yuan, HUANG Chao-zhi, YE Cheng-zhuo (Cailiao Baohu)
In order to further promote the practical application of tin plating process in electrical copper bar, tin coating with different thickness on surface of copper bar was prepared using acid tin plating process, and the influence of tin layer thickness and protective agent on appearance, contact resistance and weldability were systematically studied.Also, the corrosion resistance was studied by electrochemical scanning, neutral salt spray test and high temperature and high humidity test.Results showed that the contact resistance increased by 0.2 μΩ after the copper bar was tinned, and the different thickness of tin layer had little effect on it.Increasing the coverage of tin on the welding surface by 40% and the welding surface was more detailed with the increase of tin thickness.After 1 000 h of high temperature, high humidity and salt spray test, there was no serous corrosion.On the premise of having little effect on the contact resistance and weldability, the tin protection process improved the anti-tarnishing ability and corrosion resistance of the tin layer.At last, the corresponding tin plating protection scheme of copper bar under different service conditions was given.